Combatibility of Certain Fungicides and Insecticides Used For the Control of Major Diseases and Insect Pests Infesting the Rice Crop - Kalpana T A (Department of Plant Pathology, College of Horticulture, 1992)
The efficacy of four fungicides and four insecticides alone and in combination was studied at different concentrations recommended, three-fourth and half the recommended concentrations against two major diseases of rice namely, rice blast caused by Pyricularia oryzae Cavara and sheth blight caused by Rhizoctonia solani kahn. And two major insect-pests namely, leaffoldar Cnaphalocrocis medinalis medinalis Guen. And brown planthopper Nilaparvatha lugens stal. At tillering, panicle initiation and flowering stage of the crop. The experiment was conducted in vivo and in vitro conditions during 1989-91, at the college of Horticulture, Vellanikkara, Thrissur.